Sphingosine-1-phosphate: the Swiss army knife of sphingolipid signaling - Maceyka, Michael (American Society for Biochemistry and Molecular Biology, 2009)
The sphingolipid metabolite sphingosine-1-phosphate (S1P) and the kinases that produce it have emerged as critical regulators of numerous fundamental biological processes important for health and disease. Activation of sphingosine kinases (SphKs) by a variety of agonists increases intracellular S1P, which in turn can be secreted out of the cell and bind to and signal through S1P receptors (S1PRs) in an autocrine and/or paracrine manner. Recent studies suggest that this “inside-out” signaling by S1P may play a role in many human diseases. As the roles of the S1PRs in cell and organismal physiology are discussed elsewhere in this volume, we focus this review mainly on recent reports showing how SphKs are activated and S1P reaches its receptors, the role of SphKs and S1P in regulating sphingolipid homeostasis, and the potential importance of the SphK/S1P axis as a therapeutic target in human diseases.